Winning our children back to Islam - Lang, Jeffrey; One Islam Publications; Mecca Centre Dawah Group (N.S.W, Australia : One Islam Publications, 2006)
Dr. Lang seeks in this lecture to wake up those who claim to be Muslim and offers sincere advice to those who are contributing to the'clash' between the surrounding culture and the religious sub-culture that our youth are asked to be a part of
Title from title screen
Presenter : Jeffrey Lang
Keywords: Muslim youth -- Religious life; Muslim youth -- Conduct of life; Islam